2015
DOI: 10.1371/journal.pone.0136172
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free DNA in Human Follicular Microenvironment: New Prognostic Biomarker to Predict in vitro Fertilization Outcomes

Abstract: Cell-free DNA (cfDNA) fragments, detected in blood and in other biological fluids, are released from apoptotic and/or necrotic cells. CfDNA is currently used as biomarker for the detection of many diseases such as some cancers and gynecological and obstetrics disorders. In this study, we investigated if cfDNA levels in follicular fluid (FF) samples from in vitro fertilization (IVF) patients, could be related to their ovarian reserve status, controlled ovarian stimulation (COS) protocols and IVF outcomes. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 50 publications
3
19
0
3
Order By: Relevance
“…cfDNA concentration in human FF is known to decrease with the development of the follicle; its concentration rangs from 1 to 3 ng/μl in the antral follicles (8−12 mm in diameter) [ 9 , 15 , 16 ]. Consistent with this, the present study showed that the cfDNA content in FF decreased with follicle development, and the concentration in FF derived from S-, M-, and L-FF was 16.4 ± 0.5, 10.5 ± 0.7, and 2.2 ± 0.2 ng/μl, respectively ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cfDNA concentration in human FF is known to decrease with the development of the follicle; its concentration rangs from 1 to 3 ng/μl in the antral follicles (8−12 mm in diameter) [ 9 , 15 , 16 ]. Consistent with this, the present study showed that the cfDNA content in FF decreased with follicle development, and the concentration in FF derived from S-, M-, and L-FF was 16.4 ± 0.5, 10.5 ± 0.7, and 2.2 ± 0.2 ng/μl, respectively ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A pioneering study has shown that the amount of cfDNA in FF was related to the apoptosis of granulosa cells and that addition of cfDNA to the culture medium induced the latter [ 10 ]. On the other hand, accumulating evidence suggests that the amount of cfDNA reflects the ovarian reserve and possible outcome of in vitro fertilization [ 15 , 16 ]. In the present study, however, the phenomenon by which cfDNA (present in FF or culture medium) reflects oocyte ability and follicle condition has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…В настоящем исследовании продемонстрировано, что содержание свДНК в ФЖ женщин со стимулированной овуляцией значимо выше, чем в естественных циклах. Полученные результаты согласуются с данными других авторов, которые выявили наличие свДНК в ФЖ женщин со стимулированной овуляцией [14,[19][20][21] и показали прямую взаимосвязь между концентрацией свДНК и дозой гонадотропина [14]. Данные о наличии свДНК в ФЖ женщин в естественных циклах ранее в литературе не освещались и, учитывая иммуномодулирующие свойства ДНК [5], могут послужить основой для исследования новых аспектов иммунно-ýндокринных взаимодействий в регуляции фолликулогенеза и созревания ооцитов.…”
Section: Discussionunclassified
“…Так, S. Traver и соавт. выявили повышенный уровень свДНК в группе женщин с СПКЯ [14]. В настоящем исследовании продемонстрировано, что наличие большого числа АФ (>14) у женщин с мультифолликулярными яичниками также ассоциируется с высокой концентрацией свДНК.…”
Section: Discussionunclassified
See 1 more Smart Citation